Endocrine disrupting, mutagenic, and teratogenic effects of upper Danube River sediments using effect-directed analysis - Higley, Eric; Grund, Stefanie (Environmental toxicology and chemistry, 2012)
Effect-directed analysis (EDA) can be useful in identifying and evaluating potential toxic chemicals in matrixes. Previous investigations of extracts of sediments from the upper Danube River in Germany revealed acute nonspecific and mechanism-specific toxicity as determined by several bioassays. In the present study, EDA was used to further characterize these sediments and identify groups of potentially toxic chemicals. Four extracts of sediments were subjected to a novel fractionation scheme coupled with identification of chemicals to characterize their ability to disrupt steroidogenesis or cause mutagenic and/or teratogenic effects. All four whole extracts of sediment caused significant alteration of steroidogenesis and were mutagenic as well as teratogenic. The whole extracts of sediments were separated into 18 fractions and these fractions were then subjected to the same bioassays as the whole extracts. Fractions 7 to 15 of all four extracts were consistently more potent in both the Ames fluctuation and H295R assays. Much of this toxicity could be attributed to polycyclic aromatic hydrocarbons, sterols, and in fraction 7-naphthoic acids. Because the fraction containing polychlorinated biphenyls, polychlorodibenzodioxin/furan, dichlorodiphenyltrichloroethane, and several organophosphates did not cause any observable effects on hormone production or a mutagenic response, or were not detected in any of the samples, these compounds could be eliminated as causative agents for the observed effects. These results demonstrate the value of using EDA, which uses multiple bioassays and new fractionation techniques to assess toxicity. Furthermore, to our knowledge this is the first study using the recently developed H295R assay within EDA strategies.
First published: 13 February 2012
Gesehen am 20.06.2018